Our system is currently under heavy load due to increased usage. We're actively working on upgrades to improve performance. Thank you for your patience.
2022
DOI: 10.1021/acsaem.2c01333
|View full text |Cite
|
Sign up to set email alerts
|

Antimony Doping of CsBi3I10 for Tailoring the Film Morphology and Defects toward Efficient Lead-Free Thin-Film Solar Cells

Abstract: The CsBi3I10 (CBI) semiconductor as a light absorber emerges as a promising alternative to lead-based perovskites owing to its low toxicity, good stability, and satisfying physical properties. However, CBI exhibits an uncontrollable crystallization process, poor film morphology, high defect density, and short carrier lifetime, which lead to inferior optoelectronic properties, limiting its practical application in solar cell devices. Here, the Sb doping strategy is successfully developed for CBI films by a one-… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
11
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
4
1

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(12 citation statements)
references
References 39 publications
1
11
0
Order By: Relevance
“…We have compared our findings with recent literature in Table 1. The obtained results showed that our findings are comparable with previous reports [33–45] …”
Section: Resultssupporting
confidence: 93%
See 3 more Smart Citations
“…We have compared our findings with recent literature in Table 1. The obtained results showed that our findings are comparable with previous reports [33–45] …”
Section: Resultssupporting
confidence: 93%
“…The lowest PL intensity was observed for FTO/TiO 2 /CsBi 3 I 10 /GO+spiro‐OMeTAD (Figure S3). The lowest intensity suggested the better charge‐extraction and transfer in FTO/TiO 2 /CsBi 3 I 10 /GO+spiro‐OMeTAD compare to the FTO/CsBi 3 I 10 and FTO/TiO 2 /CsBi 3 I 10 [44] …”
Section: Resultsmentioning
confidence: 98%
See 2 more Smart Citations
“…Bismuth (Bi)-based perovskite analogue CsBi 3 I 10 (CBI) exhibits a small bandgap (1.77 eV), high visible light absorption, and excellent humidity tolerance as well as low toxicity, making it become one of the most promising candidates for Pb-free perovskite solar cells. 6,7 Some early attempts such as solvent engineering, 8 additive strategies, 9 element doping 10 and charge transport layer optimization 11,12 have been adopted to further explore and improve the photoelectric properties of CsBi 3 I 10 film solar cells. However, CsBi 3 I 10 is still not dazzling due to its lower PCEs compared to other bismuth-based materials such as Cs 2 AgBiBr 6 , 13,14 Cs 3 Bi 2 I 9 4,15 and AgBiS 2 .…”
Section: Introductionmentioning
confidence: 99%